Apparel retailing in the Philippines a study of six selected local apparel franchises - Martinez, Karmina Isabel L.; Escano, Maria Monica R. (2005.)
This is a descriptive study of six (6) selected apparel franchises which are home grown, retailing women's apparel, and whose target market falls into the 13-34 age bracket. An initial list was narrowed down to six(6) based on the number of boutiques/outlets all over the country, the latest gross sales data available, and the availability of information. The selected franchises were Bayo, Bench, Folded & Hung, Kamiseta, Penshoppe, and Plains and Prints. The objective of the study was to put together the profile of six (6) selected local apparel franchises to serve as a guide to the prospective franchisee. With so many available franchises to choose from, it is not possible to investigate them all. The profile consists of demographic information-age of the franchise, target market, distribution/location throughout the country, and basic franchise information-franchise fee/investment, return of investment, renewal, advertising and marketing fees. Data were sourced from the documentary research, primers and promotional literatures, trade and industry statistics, and business publications. Supplementary information were gathered from interviews of franchisees but the researcher had to contend with time and confidentiality constraints. The open-ended questions asked intended to find out how they got started in the business, issues which were important to them, and their advice to prospective franchisees. A comparative description of the franchises were presented. The results were organized in charts, tables and graphs. The results show that of the six (6), Penshoppe and Bench have been in the market the longest; Penshoppe since 1986 and Bench since 1987. Bench ranked number one in the number of stores followed by Penshoppe. Bayo appears to have the best gross profit to number of stores ratio while Kamiseta is the fastest growing with 19 franchises in only five (5) years. Penshoppe and Folded & Hung have no local franchisee to date but the former has two (2) international franchises. While all six (6) are into 13-34 age market, Plains and Prints is decidedly geared towards the young working women. A survey question asked the respondents to rank four (4) factors in the decision to buy a franchise, namely: franchise fee/investment, perceived profitability, familiarity/interest with the product, and brand image/name. Results show that while as predicted perceived profitability was ranked ass most important (53%), the amount of the franchise investment was as crucial for nearly half of the respondents (47%). This suggests a realist's attitude which places a limit on one's desired economic rewards within one's financial capability. Franchising has become the most favored entry point in the retailing business in the country today. The selection process is very crucial. The usefulness of this research lies in the extent to which it has filled a gap in the body of literature pertaining to apparel franchising in the country and based on these, drawn up a guide in the search for the franchise.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Philippines; Retail trade